Relações anafóricas em perguntas de compreensão em leitura em língua estrangeira: o papel da anáfora estabelecida entre elementos das perguntas e seus referentes na superfície textual - Vale, Daisy Rodrigues do (1998)
The complexity of the process of reading in English as a foreign language (LE) has attracted linguists and language teachers from all over the world, who aim to obtain the most accurate theory that explains how people turn texts into significant units. In my experience as a language teacher, a question: “How do teachers or examiners design tests for reading comprehension and what are their expectations regarding performance students in each type of question or comprehension question? ” . To answer this question, some categories of questions from Reading comprehension were elaborated based on cohesive relationships anaphorics established between the elements of the questions and 03 respective referents on the textual surface. Such categorization aimed to verify how this anaphor interferes with the reading performance of English students - LE do ensino fundamental and how this categorization could subsidize language teachers to classify reading comprehension questions according to the degree of difficulty generated by each question category. The subjects involved in this research comprise two groups of approximately 26 students from 88 grade of elementary school. They read the same texts and answered some comprehension questions. The questions for both groups asked for equal answers, however, some of these questions presented to them in a different way, that is, their elements established different anaphretic relationships with those on the textual surface. The responses obtained were corrected according to the information requested by the question, then analyzed and finally, classified according to the degree of difficulty. The relationship established by the interrogative preforms and the type of referent required by them was also analyzed, to verify if the relation established is obvious to the subjects or not. The results obtained reveal that the anaphor influences the performance of Readers when answering essay questions for reading comprehension, or that is, influences understanding in reading comprehension questions.